STUDY OF MAKING POLYESTER RESIN MATRIX COMPOSITES USING BASALT SCORIA POWDER FILLERS TO TENSILE STRENGTH AND COMPRESSIVE STRENGTH - David Candra Birawidha; Kusno Isnugroho; Yusup Hendronursito; Muhammad Amin; Muhammad Al Muttaqii (SINERGI, 2021)
An experimental study on the manufacture of polyester resin matrix composites using basalt powder as a reinforcing filler has been carried out. Basalt is a volcanic igneous rock often found in East Lampung and has not been utilised. Basalt is chosen as a reinforcing filler because basalt has advantages such as wear resistance, corrosion resistance, resistance to chemical reactions, and high hardness. The research parameters used were variations in the size of the basalt powder, the composition of the polyester resin matrix to the basalt powder, and the percentage of the catalyst. All parameters were mixed according to the research procedure, and all samples were formed under pressure 20 kN. Tensile test results showed the highest value of 0.961 kgf/mm2 from 60 mesh-25% polyester-1/30 catalyst variation parameter. The highest compressive strength value of 28.331 kgf/mm2 was obtained from the various parameters of 270 mesh-20% polyester-1/20 catalyst and 270 mesh-25% polyester-1/30 catalyst. The results were not much different from those, which is 27.787 kgf/mm2. The use of 1/30 hardener catalyst to the amount of polymer by 25 %wt gives optimal results on the characterisation material testing. However, the effect of the filler grain size gave different results for each test carried out. Therefore, to obtain the desired mechanical properties when using basalt rock powder as a filler, it is necessary to pay attention to the correct grain size.